Enhancing Employability Skills and Placements in Technical Institutes: A Case Study - Shahabadkar, Pramod K.; Joshi, Ajinkya S.; Nandurkar, Keshav N. (Journal of Engineering Education Transformations, 2021)
Objective: Employability skills and placements are extremely important for any technical institute. Analysis of strengths, weakness, opportunities and challenges (SWOC) helps to make informed decisions on the inputs received from the stakeholders. The purpose of this paper is to identify the SWOC of training and placement cell of a technical institute, undertake initiatives based on the SWOC analysis and determine the impact of these initiatives. Methodology: IT tools like Google form were designed and employed to carry out the SWOC analysis. This Google form was sent to the students and responses were obtained from 1087 students. The students responses were grouped under strengths, weaknesses, opportunities and challenges and then segregated under five sub categories namely - institute and infrastructure; staff; teaching and learning; training/placement activities and mechanism or policies for improvement. Based on the SWOC analysis, certain initiatives were undertaken to overcome the weakness and to explore the opportunities. These initiatives have been mapped with the SWOC are analysed to determine the impact. To remain within the scope of this paper, data related to training and placement activities are presented in this paper. This SWOC analysis has been conducted in an engineering college located in the western part of India in the state of Maharashtra. Findings: Findings indicate that there has been a significant improvement in the number of placements, average package and industry footfall following the implementation of the initiatives. Average placements increased by 36.03%, average package increased by 2.31%, maximum package increased by 40% and industry footfall increased by 35%. According to the recruiter feedback, a satisfactory increase of around 10 to 15 % has been observed in the leadership skills, overall behaviour and sincerity of the students. Limitations: The present study has considered only the activities related to training and placement cell for enhancing the employability skills and placements in the institute. A larger study including other categories needs to be undertaken. Social Implications: The analysis is based on the opinion of the students, faculty, recruiters and actual values obtained after the implementation of the initiatives. Authors believe that a similar process with suitable modifications can be adopted to enhance the employability skills of students and placements of any educational institute. Originality: This study is original in the sense that data is collected directly from the students. Further, in this study systematic mapping of SWOC analysis, initiatives undertaken and outcome of these initiatives is being carried out. The outcome of this study will help the Management, Principal and other senior faculty in developing appropriate strategies for enhancing the employability skills and placements.